Exploring the Vietnamese Immigrants' Experience in Hungary: an Intersectional Analysis - Kha Tran (Különleges Bánásmód)
The way Vietnamese immigrants in Budapest negotiate their multiple identities is by all means but simple. It is a mix of personal belongings, culture, and how society sees them. In today’s more and more globalized world, people move between different cultures all the time, adjusting themselves to new social rules and expectations. Identity is not something fixed—it changes all the time, influenced by both a person’s background and the pressure to fit into the new society. For Vietnamese immigrants in Budapest, this idea means trying to keep their traditions and connections to their community while also finding a place in Hungarian society. In this process, big questions come up: Where do they belong? Are they accepted or excluded? How do they define themselves? The immigrant experience is often full of mixed feelings—sometimes they feel close to both cultures, sometimes they feel distant from both. They are always rethinking where they stand between their old home and their new. This paper attempts to explore the ways Vietnamese immigrants in Budapest navigate through the host society while balancing their multiple identities in a multicultural context.